2021
DOI: 10.1136/jitc-2021-002417
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenomic determinants of tumor microenvironment correlate with superior survival in high-risk neuroblastoma

Abstract: BackgroundTumor-infiltrating CD8+ T cells and neoantigens are predictors of a favorable prognosis and response to immunotherapy with checkpoint inhibitors in many types of adult cancer, but little is known about their role in pediatric malignancies. Here, we analyzed the prognostic strength of T cell-inflamed gene expression and neoantigen load in high-risk neuroblastoma. We also compared transcriptional programs in T cell-inflamed and non-T cell-inflamed high-risk neuroblastomas to investigate possible mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Further to the association of expression of these TFs with patient survival, previous studies have linked their expression with various immune cells in the TME [ 27 ], leading us to address the impact of MES and ADRN TFs on the TME.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further to the association of expression of these TFs with patient survival, previous studies have linked their expression with various immune cells in the TME [ 27 ], leading us to address the impact of MES and ADRN TFs on the TME.…”
Section: Resultsmentioning
confidence: 99%
“…In NB, T-cell infiltration to the tumour microenvironment (TME), correlates with enhanced patient overall survival (OS). Specifically, the expression and activation of MYCN, ASCL1, and SOX11 are inversely correlated with T-cell infiltration in NB and correlate with patient OS [ 27 ], supporting the significance of these TFs in the NB TME. Notably, similar associations between MES and ADRN TFs with the infiltration of cancer-associated fibroblasts (CAFs) of the TME implicate these TFs in pro-tumourigenic remodelling of the TME in cancers [ 28 – 31 ].…”
Section: Introductionmentioning
confidence: 99%
“… 35 These suggested that a higher cytolytic score resulting from neoantigen load did not yield a better prognosis in MM, although a high neoantigen load and tumor-infiltrating CD8+ T cells have been reported to imply a better survival in some solid tumors, such as melanoma and neuroblastoma. 36 , 37 This might indicate a difference between low- and high-TMB tumors.…”
Section: Discussionmentioning
confidence: 99%
“…showed that tumor-infiltrating T cells, mainly CD3+, CD4+, and CD8+ T cells, improved clinical outcomes of patients with therapy-resistant NB ( 18 ) whereas Riyue et al. demonstrated that patients with high-risk NB showed a better survival when the tumor was T cell inflamed ( 19 ). A detailed description of the phenotypes of all infiltrating T cells, especially CD3+ T cells, CD8+ cytotoxic T cells, and CD45RO+ memory T cells, using a large collection of NB specimens is however currently not available.…”
Section: Introductionmentioning
confidence: 99%